Increasing Activity and Learning Achievement in Mathematics with Think Pair Share by Beach Balls - Janah, Siti Nur (Universitas Sebelas Maret, 2022)
The purpose of this study was to increase the activity and achievement of learning mathematics for 4 grade students of SD Negeri 1 Kunti with the Think Pair Share (TPS) cooperative learning model by beach balls. This study uses the Classroom Action Research (CAR) method, namely action research which consists of 2 cycles. The stages of each cycle are planning, implementing, observing and reflecting. In the first cycle of learning activities, an average score of 68.92 was obtained. In cycle II it increased to 75.00. The percentage of completeness activities was 70.83%, increasing to 100%. The average student achievement in mathematics increased from 61.54 to 65.00 in the first cycle and 65.59 in the second cycle. These results indicate that the Think Pair Share (TPS) type of cooperative learning model accompanied by Beach Ball can increase the activity and learning achievement of Class IV Mathematics at SD Negeri 1 Kunti.